Burya A.I., Tomina A.-M.V. The effect of heat-resistant polysulfonamide fiber on the tribological properties of organoplastic based on phenylone C-1 - Буря, О.І.; Томіна, А.-М.В. (Problems of Tribology, 2017)
Over the past few years there have been revolutionary changes in the automotive industry, in the manufacture of brake linings associated primarily with a radical increase in the proportion of friction composite materials (FCM), which are a multipurpose material that characterizes progress in this industry: improving quality; improving overall reliability; cost optimization; weight reduction; increased corrosion resistance. In the coming years, the use of domestic friction non-asbestos composite materials possessing high heat resistance and wear resistance at high mechanical strength, reinforced with various types of fibers in particular organic ones, seems promising in modern vehicles, the common advantages of which are low mass, high specific characteristics at stretching, high fracture toughness, chemical and electromagnetic inertness. The article deals with the non-asbestos frictional polymeric composite material on the basis of aromatic polyamide phenylone C-1 containing 5-20 wt% of heat-resistant polysulfonamide fiber brand Tanlon T700. According to the results of the tests it was established that the reinforcement of the initial polymer with polysulfonamide fiber reduces the intensity of linear wear and friction coefficient by 5-15 and 12% respectively, which will allow application of the developed material in the brake friction units of machines and mechanisms that used in machine building, chemical, textile industry and others. Keywords: organoplastic, polysulfonamide, coefficient of friction, wear, frictional polymer composition, brake hubs.